Effectiveness of union disaster management committee for flood disaster management: a comparative srudy - Uddin, Shah Mujahid (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2013.